Homérico χλωρὸν δέος. El significado de χλωρός en la poesía griega arcaica (Minerva, 2019)
The aim of this paper is to analyze the adjective χλωρός in the archaic poetry, in order to clarify his original meaning, perhaps outside the semantic fiel of colour. Χλωρός as ‘pale’ is a perfectly attested use in the medical texts, but not in the archaic poetry. Our interpretation concerns especially the homeric formula χλωρὸν δέος.
Keywords: χλωρός; Homer; archaic Greek poetry; colour adjectives; χλωρός as ‘pale’; χλωρὸν δέος